Disc Rehydration after Dynamic Stabilization: A Report of 59 Cases - Atilla Yilmaz; Salim Senturk; Mehdi Sasani; Tunc Oktenoglu; Onur Yaman; Hakan Yildirim; Tuncer Suzer; Ali Fahir Ozer (Asian Spine Journal, 2017)
Study DesignA retrospective study investigating decrease in the nucleus pulposus signal intensity or disc height on magnetic resonance imaging (MRI) and disc degeneration.PurposeAlthough a degenerated disc cannot self-regenerate, distraction or stabilization may provide suitable conditions for rehydration and possible regeneration. This study aimed to evaluate clinical outcomes and disc regeneration via MRI in a series of patients with degenerative disc disease (DDD) who underwent lumbar stabilization with a dynamic stabilization system (DSS).Overview of LiteratureA dynamic system provides rehydration during early DDD.MethodsFifty-nine patients (mean age, 46.5 years) who undedwent stabilization with DSS for segmental instability (painful black disc) between 2004 and 2014 were retrospectively evaluated. All patients underwent MRI preoperatively and 12 months postoperatively. Intervertebral disc (IVD) degeneration grades at the implanted segment were categorized using the Pfirrmann classification system. Patients were followed for a mean of 6.4 years, and clinical outcomes were based on visual analog scale (VAS) and Oswestry disability index (ODI) scores.ResultsSignificant improvements in back pain VAS and ODI scores from before surgery (7 and 68%, respectively) were reported at 6 (2.85 and 27.4%, respectively) and 12 months postoperatively (1.8 and 16.3%, respectively). Postoperative IVD changes were observed in 28 patients. Improvement was observed in 20 patients (34%), whereas progressive degeneration was observed in eight patients (13.5%). Thirty-one patients (52.5%) exhibited neither improvement nor progression. Single Pfirrmann grade improvements were observed in 29% of the patients and two-grade improvements were observed in 5%.ConclusionsOur observations support the theory that physiological movement and a balanced load distribution are necessary for disc regeneration. We conclude that DSS may decelerate the degeneration process and appears to facilitate regeneration.